The Burial Mound Sites of Imperial Central Tibet, Map scale 1:800.000 - Kriz, Karel (Verlag der Österreichischen Akademie der Wissenschaften, 2020)
The map illustrates the position of the burial mound fields in Central Tibet that have been registered so far by the "Tibetan tumulus project", an Austrian Science Fund (FWF) financed long-term research conducted at the Austrian Academy of Sciences' Institute for Social Anthropology (ISA). The entries of districts and key political sites related to the time of the Tibetan Empire (7th-9th cent. CE) form the relevant historical reference for this distribution map. This reveals a tumulus landscape of enormous concentration in the relatively small geographic area of Central Tibet (Dbus-Gtsang region), which in geographical, economic and political terms formed the heartland of the Tibetan Empire.